2020
DOI: 10.17977/um039v5i12020p001
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian Undergraduate EFL Students’ Perceptions toward Flipped Classroom

Abstract: Tujuan dari penelitian ini adalah untuk menemukan persepsi mahasiswa EFL Indonesia terhadap penerapan flipped classroom. Penelitian ini menggunakan desain survey dan data dikumpulkan melalui kuesioner dan disebarkan kepada 30 siswa yang mengalami implementasi flipped classroom. Kuesioner terdiri dari dua aspek, yaitu aspek kebermaknaan dan kompetensi. Hasil kuesioner dihitung secara statistik. Data pada aspek kebermaknaan mengungkapkan bahwa sebagian besar siswa memiliki persepsi positif terhadap pelaksanaan f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Studies on flipped learning-focused either on experimental research designs (Ahmed, 2016; Obari and Lambacher, 2015; Singay, 2020a) or on assessing students’ attitudes towards using the flipped learning (Maharani et al , 2020; Sunday, 2020b). Ashwin and Mcvitty (2015, p. 345) stated that “engagement can help students to improve their learning outcomes”.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on flipped learning-focused either on experimental research designs (Ahmed, 2016; Obari and Lambacher, 2015; Singay, 2020a) or on assessing students’ attitudes towards using the flipped learning (Maharani et al , 2020; Sunday, 2020b). Ashwin and Mcvitty (2015, p. 345) stated that “engagement can help students to improve their learning outcomes”.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies on the flipped learning put a focus either on assessing students' attitudes towards using the flipped learning (Maharani et al, 2020;Singay, 2020b) or on improving language skills (Ahmed, 2016;Obari and Lambacher, 2015;Singay, 2020a). Flipped learning is found to improve EFL language skills specially oral skills.…”
Section: Introductionmentioning
confidence: 99%
“…The use of ICT as teaching media in EFL classroom is able to solve the problem and help teachers design new techniques in teaching; it also encourages student willingness to learn English and implement enjoyable learning activities (Fithri Al-Munawwarah, 2014). Study that examines the use of ICT for learning conducted by Maharani et al (2020) researched students' perceptions of the flipped classroom, which is a combination of e-learning and face-to-face instructional principles by integrating activities, resources, support, and assessment. Supported by the students' perception of the implementation of the flipped classroom, it is observed that flipped classroom was an effective learning method to enhance Indonesian undergraduate students' writing competence (Maharani et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Study that examines the use of ICT for learning conducted by Maharani et al (2020) researched students' perceptions of the flipped classroom, which is a combination of e-learning and face-to-face instructional principles by integrating activities, resources, support, and assessment. Supported by the students' perception of the implementation of the flipped classroom, it is observed that flipped classroom was an effective learning method to enhance Indonesian undergraduate students' writing competence (Maharani et al, 2020). Another study related about the use of ICT in teaching and learning was study by Noriega (2016), in this study, the effect of Mlearning on the development of students' writing skills was examined, and it was found that the use of mobile devices can increase students' attention and encouragement to improve their writing skills.…”
Section: Introductionmentioning
confidence: 99%